Murraya koenigii leaf extract inhibits proteasome activity and induces cell death in breast cancer cells - Noolu Bindu; Ajumeera Rajanna; Chauhan Anitha; Nagalla Balakrishna; Manchala Raghunath; Ismail Ayesha (BMC, 2013)
Abstract Background Inhibition of the proteolytic activity of 26S proteasome, the protein-degrading machine, is now considered a novel and promising approach for cancer therapy. Interestingly, proteasome inhibitors have been demonstrated to selectively kill cancer cells and also enhance the sensitivity of tumor cells to chemotherapeutic agents. Recently, polyphenols/flavonoids have been reported to inhibit proteasome activity. Murraya koenigii Spreng, a medicinally important herb of Indian origin, has been used for centuries in the Ayurvedic system of medicine. Here we show that Murraya koenigii leaves (curry leaves), a rich source of polyphenols, inhibit the proteolytic activity of the cancer cell proteasome, and cause cell death. Methods Hydro-methanolic extract of curry leaves (CLE) was prepared and its total phenolic content [TPC] determined by, the Folin-Ciocalteau's method. Two human breast carcinoma cell lines: MCF-7 and MDA-MB-231 and a normal human lung fibroblast cell line, WI-38 were used for the studies. Cytotoxicity of the CLE was assessed by the MTT assay. We studied the effect of CLE on growth kinetics using colony formation assay. Growth arrest was assessed by cell cycle analysis and apoptosis by Annexin-V binding using flow cytometry. Inhibition of the endogenous 26S proteasome was studied in intact cells and cell extracts using substrates specific to 20S proteasomal enzymes. Results CLE decreased cell viability and altered the growth kinetics in both the breast cancer cell lines in a dose-dependent manner. It showed a significant arrest of cells in the S phase albeit in cancer cells only. Annexin V binding data suggests that cell death was via the apoptotic pathway in both the cancer cell lines. CLE treatment significantly decreased the activity of the 26S proteasome in the cancer but not normal cells. Conclusions Our study suggests M. koenigii leaves to be a potent source of proteasome inhibitors that lead to cancer cell death. Therefore, identification of active component(s) from the leaf extract could lead to the development of anti-cancer agents which could be useful in the treatment of different types of cancers.